An Efficient Genetic Transformation and CRISPR/Cas9-Based Genome Editing System for Moso Bamboo (Phyllostachys edulis) - Huang, Biyun; Zhuo, Renying; Fan, Huijin; Wang, Yujun; Xu, Jing; Jin, Kangming; Qiao, Guirong (Frontiers in Plant Science, 2022)
Moso bamboo (Phyllostachys edulis) is the most important monopodial bamboo species worldwide. Without a genetic transformation system, it is difficult to verify the functions of genes controlling important traits and conduct molecular breeding in moso bamboo. Here, we established a plant regeneration system from immature embryos. Calli were induced on MS medium added 4–6 mg⋅L–1 2,4-dichlorophenoxyacetic acid (2,4-D) with high efficiency (>60%). A plant growth regulator combination of 0.5 mg⋅L–1 1-naphthylacetic acid (NAA), 2.0 mg⋅L–1 6-benzylaminopurine (BAP), and 3.0 mg⋅L–1 zeatin (ZT) was suitable for shoot differentiation, and the shoot induction frequency was increased to 43% after 0.5 mg⋅L–1 abscisic acid (ABA) pretreatment. An effective antibiotic screening concentration was determined by hygromycin sensitivity test. We further optimized the Agrobacterium concentration and added vacuum infiltration for infection, which improves the transient expression efficiency. A genetic transformation system was established for the first time in moso bamboo, with the transformation efficiency of approximately 5%. To optimize genome editing, two endogenous U3 small nuclear RNA (snRNA) promoters were isolated and used to drive small guide RNA (sgRNA) expression. The results showed that the PeU3.1 promoter exhibited higher efficiency, and it was used for subsequent genome editing. Finally, homozygous pds1pds2 mutants were obtained by an efficient CRISPR/Cas9 genome-editing system. These technical systems will be conducive to gene functional validation and accelerate the molecular breeding process of moso bamboo.